The Influence Of Lifestyle And Hedonic Shopping Value On Impulsive Shopee Buying Behavior In East Java - Evi Yulia; Muhamad Imam Syairozi; Sani Rusminah (Jurnal Multidisiplin Sahombu, 2024)
This study aims to determine the influence of lifestyle and hedonic shoping value on impulse buying behavior. The research method used in this study is quantitative research using questionnaires as data collection instruments. The population in this study is Shopee customers with a sample of 96 respondents using the purposive sampling technique. The results of the study show that lifestyle variables and hedonic shoping value have a positive and significant influence on impulse buying behavior. While the most dominant variable affecting impulse buying behavior is hedonic shoping value because hedonic behavior tends to make a person motivated to make impulse purchases, this behavior makes a person happy and happy. The outline of this study shows that lifestyle and hedonic shoping value are effective stimuli in increasing impulsive buying behavior